2017
DOI: 10.1002/jemt.22926
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and distribution of antennal sensilla of the chilli thripsScirtothrips dorsalishood (Thysanoptera: Thripidae)

Abstract: The chilli thrips, Scirtothrips dorsalis Hood, is a serious pest of numerous important vegetable and ornamental crops. Various signals, especially phytochemical cues, determine the behavior of the phytophagous thrips at host selection. The sensory abilities of S. dorsalis are poorly understood although the antennae of adult are known to possess important sensory structures in orther insects. In this study, the morphology, distribution, and ultrastructure of the antennal sensilla of the S. dorsalis were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 68 publications
3
18
0
Order By: Relevance
“…In Thysanoptera, antennal sensilla have diverse shapes and are highly structurally modified, even in different species within the same genera [4]. A division in subtypes was difficult given their variability in shape at the same position [5].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Thysanoptera, antennal sensilla have diverse shapes and are highly structurally modified, even in different species within the same genera [4]. A division in subtypes was difficult given their variability in shape at the same position [5].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ding [22] identified four subtypes of sensilla basiconica in the adults of F. occidentalis based solely on their shape, but De Facci [5] thought three of these subtypes (BIII, a putative DW, BIV and BV) may be sensilla chaetica. In addition, Ding [22] stated the presence of U-shaped sensilla, but Zhu [4] and Li [23] both named this morphological type of sensillum sensilla basiconica. A recent study on the antennal sensilla of Scirtothrips dorsalis Hood found, using TEM, that sensilla chaetica II had a relatively thick wall and lumen and was innervated by a single unbranched dendrite that terminated in a tubular body.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations